Círculos discursivos, juventudes e dispositivos de segurança pública: paisagens do Guajuviras, território de paz - Rosa, Cristiano Neves da (Universidade do Vale do Rio dos Sinos, 2012)
This dissertation parts from a general concern about the political investment over the bodies throughout the western society history, investment that transforms individuals in a social subject. To elucidate this case, we reference public safety programs implemented in Brazil, where inhabitants of slums and outskirts have been targeted by a series of actions which seem to remember what philosopher Gilles Deleuze (2006) conceptualized as “society of control”. Starting from Michel Foucault’s discourse analysis (1986, 2011), it is focused and questioned how the discursive production, over the years, positioned a neighborhood of the city of Canoas, in the state of Rio Grande do Sul, constituting it as a territory to be pacified, from what José Geraldo Soares Damico (2011) called public safety and participation devices. The purpose of this study is not to descant about safety policies, taking sides. It is proposed, based on an approach influenced by the works of Michel Foucault (1984, 1986, 1995, 2008, 2009, 2011), to make a critical analysis of the way which certain places, understood as socially vulnerable, were selected to be invested with specific public safety actions, transforming them into a society of control. The field of study is the Guajuviras neighborhood, located in the city of Canoas, which has been the target of several actions implemented by the Municipal Public Safety and Citizenship Secretariat, trough an agreement with the Ministry of Justice of the federal government, developing actions of the National Public Safety with Citizenship Program (Pronasci), and particularly the City’s Sport and Leisure Program (PELC), as part of the actions of this broad safety policy. Specifically, we analyze the speeches produced by young people about the place they live and the actions of the public safety policies, with particular emphasis on the way that it is presented to them, as a device of social control and construction of a specific subjectivity by which they are being affected. For a better understanding, this work makes reference to youth cultures and different forms of sociability that are experienced in multiple ways by the youngsters in this historical and local context. In The researched people have ages between 14 and 29 years old, historically positioned by violence, inhabitants of a territory to be pacified and targeted by safety and participation devices. The subjects of this research participate, now and then, in some actions of the public safety program PELC. These are the results of and ethnographic research (participant observation and field diary) recorded by the empirical contacts in the places where the activities occur.
Keywords: Produção discursiva; Dispositivos de segurança pública; Esporte e lazer; Juventudes; Sociabilidades; Discursive production; Public safety devices; Sports and leisure; Youth; Sociabilities; ACCNPQ::Ciências Humanas::Sociologia